TOPSS: TOlerability of transcranial direct current stimulation in Pediatric Stroke Survivors - Fraser, Stuart; Clearman, Anna; Abrahams, Melika; Gillick, Bernadette; Lal, Tia; Savitz, Sean; Yozbatiran, Nuray (Frontiers in Human Neuroscience, 2025)
BackgroundTranscranial direct current stimulation is a non-invasive neuromodulation technique with emerging therapeutic potential in neurodevelopmental conditions. While childhood-onset stroke survivors frequently experience long-term motor impairment, there are very few studies examining the safety and feasibility of transcranial direct current stimulation in this population.ObjectiveTo evaluate the safety, feasibility, and tolerability of bihemispheric transcranial direct current stimulation paired with occupational therapy in children and adolescents with chronic hemiparesis following childhood-onset arterial ischemic stroke or intracranial hemorrhage.MethodsIn this single-arm, open-label pilot study, five participants aged 6–19 years of age received five daily sessions of transcranial direct current stimulation (sham on day 1, then 0.5–1.5 mA) during structured occupational therapy. Safety and tolerability were assessed through side effect questionnaires, pre-and post-stimulation vital signs, and study completion rates. Secondary exploratory outcomes included arm function measures (Fugl-Meyer Assessment of Upper Extremity, perceived performance and satisfaction) (Canadian Occupational Performance Measure), and gross manual dexterity (Box and Blocks Test).ResultsAll participants completed the study with no major adverse events. Mild, self-limited itching or tingling occurred in 40% of sessions and did not limit participation. Four of five participants demonstrated clinically significant improvement on the Fugl-Meyer Assessment of the Upper Extremity at 3-month follow up. Improvements were also observed in the Canadian Occupational Performance Measure and satisfaction scores. One participant with a prior craniectomy tolerated stimulation without adverse events.ConclusiontDCS was well-tolerated in children and adolescents with chronic hemiparesis from childhood-onset stroke. These findings support the feasibility of transcranial direct current stimulation in this population and provide early-stage evidence to guide future randomized controlled trials exploring therapeutic applications of neuromodulation in childhood-onset stroke recovery.Clinical trial registrationThe study was registered on September 21, 2024, with the identifier number NCT05812794.